Interactions between engineered nanoparticles (ENPs) and plants: Phytotoxicity, uptake and accumulation - Ma, Xingmao; Geiser-Lee, Jane; Deng, Yang; Kolmakov, Andrei (The Science of the total environment, 2010)
The rapid development and potential release of engineered nanoparticles (ENPs) have raised considerable concerns due to the unique properties of nanomaterials. An important aspect of the risk assessment of ENPs is to understand the interactions of ENPs with plants, an essential base component of all ecosystems. The impact of ENPs on plant varies, depending on the composition, concentration, size and other important physical chemical properties of ENPs and plant species. Both enhancive and inhibitive effects of ENPs on plant growth at different developmental stages have been documented. ENPs could be potentially taken up by plant roots and transported to shoots through vascular systems depending upon the composition, shape, size of ENPs and plant anatomy. Despite the insights gained through many previous studies, many questions remain concerning the fate and behavior of ENPs in plant systems such as the role of surface area or surface activity of ENPs on phytotoxicity, the potential route of entrance to plant vascular tissues and the role of plant cell walls in internalization of ENPs. This article reviewed the current knowledge on the phytotoxicity and interactions of ENPs with plants at seedling and cellular levels and discussed the information gap and some immediate research needs to further our knowledge on this topic.